Performance prediction of a solar district cooling system in Riyadh, Saudi Arabia – A case study. (15th June 2018) - Franchini, G.; Brumana, G.; Perdichizzi, A.
Highlights: The operation of solar district cooling systems is investigated. The optimal size of each component is determined for the primary cost minimization. Efficiency of 2-stage chiller with PTC is higher than 1-stage chiller with ETC . Plant configuration based on PTC and 2-stage chiller is more cost effective (−30%). Abstract: The present paper aims to evaluate the performance of a solar district cooling system in typical Middle East climate conditions. A centralized cooling station is supposed to distribute chilled water for a residential compound through a piping network. Two different solar cooling technologies are compared: two-stage lithium-bromide absorption chiller ( 2sABS ) driven by Parabolic Trough Collectors ( PTCs ) vs. single-stage lithium-bromide absorption chiller ( 1sABS ) fed by Evacuated Tube Collectors ( ETCs ). A computer code has been developed in Trnsys® (the transient simulation software developed by the University of Wisconsin) to simulate on hourly basis the annual operation of the solar cooling system, including building thermal load calculation, thermal losses in pipes and control strategy of the energy storage. A solar fraction of 70% was considered to size the solar field aperture area and the chiller capacity, within a multi-variable optimization process. An auxiliary compression chiller is supposed to cover the peak loads and to be used as backup unit. The two different solar cooling plants exhibit strongly different performance. For each plant configuration, the model determined the optimal size of every component leading to the primary cost minimization. The solar district cooling configuration based on 2sABS and PTCs shows higher performance at Riyadh (KSA) climate conditions and the overall cost is 30% lower than the one of the single-stage absorption chiller plant.